2008
DOI: 10.1001/jama.299.14.1690
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Free Fatty Acids for the Maintenance of Remission in Crohn Disease

Abstract: tain remission in Crohn disease is an unmet medical need. Although formulations of 5-aminosalicylic acid agents remain widely used for this purpose, strong evidence exists that they are not effec-tive. 1 Immunosuppressive agents such as purine antimetabolites, 2,3 methotrexate, 4 and tumor necrosis factor ␣ antagonists 5-8 are moderately effective for maintaining remission; however, their use is associated with an increased risk of infection. 9-11 Therefore, development of a safe, inexpensive, and effective or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
162
2
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(171 citation statements)
references
References 42 publications
(46 reference statements)
1
162
2
6
Order By: Relevance
“…Indeed, some of the studies that have reported such benefit have been conducted in populations where the fish consumed are lean and relatively deficient in -3 PUFAs (36,37). Interventional prospective trials of fish oil supplements have given encouragement that there might be benefit (38 -40), although the results have varied (41)(42)(43)(44). Because EPA and DHA possess more double bonds than AA, they may be more susceptible to oxidation by free radicals than is AA.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some of the studies that have reported such benefit have been conducted in populations where the fish consumed are lean and relatively deficient in -3 PUFAs (36,37). Interventional prospective trials of fish oil supplements have given encouragement that there might be benefit (38 -40), although the results have varied (41)(42)(43)(44). Because EPA and DHA possess more double bonds than AA, they may be more susceptible to oxidation by free radicals than is AA.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial of 738 patients found no effect of n-3 fatty acid supplementation during 1 year in prevention of CD relapse [53], whereas other studies have found n-3 fatty acid (fish oil) supplementation to be associated with absence of relapse in CD [54]. In UC, no effect of n-3 fatty acid supplementation has been found in a meta-analysis or in a systematic review [43].…”
Section: Impact Of Diet On Disease Course and Treatment Resultsmentioning
confidence: 99%
“…The soundest result was the potential of n-3 PUFA to maintain the patients of Crohn's disease in remission (Belluzzi et al, 1996). However, this observation was not confirmed in a recent larger study using a similar protocol (Feagan et al, 2008). One reason why dietary lipids might be more effective in animal models than in human patients is the different dose of assay.…”
Section: Trials In Human Patientsmentioning
confidence: 98%